Retrospective Analysis of Spinal Radiographs for the Presence of Lumbosacral Transitional Vertebra in Patients with Axial Spondyloarthritis - Zerrin Kasap; Evren Er (Archives of Rheumatology, 2025)
Background/Aims: Axial spondyloarthritis (axSpA) is characterized by low back pain and sacroiliitis. It is important to exclude other causes of sacroiliitis before diagnosing axSpA. We hypothesized that the presence of lumbosacral transitional vertebra (LSTV) might lead to diagnostic confusion in axSpA. This study aimed to investigate the prevalence of LSTV in axSpA patients and whether LSTV caused any differences in disease characteristics compared to patients without LSTV. Materials and Methods: Retrospective study of axSpA patients (>18 years) with available pelvic and lumbosacral radiographs. Patients were divided into groups based on presence of LSTV and compared for age, sex, r-axSpA prevalence, biologic DMARD usage, CRP/ESR levels, and clinical scores (ASDAS-CRP, BASDAI, BASFI, BASMI). Results: 130 patients (82 males, 48 females); 95 using biologic DMARDs; 41 had clinical scores. LSTV prevalence was 25.4% (n = 33); most common Castellvi type 1b (39.4%). No significant differences in demographics, DMARD use, inflammatory markers, or clinical scores between groups. Conclusion: No diagnostic concerns were identified in axSpA patients with LSTV, but due to high prevalence, thorough evaluation is recommended prior to axSpA diagnosis, beyond ASAS criteria alone.